Contribution to the knowledge of the Uzbek cuckoo wasps (Hymenoptera, Chrysididae) with the first checklist and descriptions of new species - Rosa, Paolo; Halada, Marek; Fateryga, Alexander V.; Proshchalykin, Maxim Yu. (Zootaxa, 2025)
An annotated checklist of the Chrysididae from Uzbekistan is presented, including a revision of the bibliographical data and recently collected material. The known Uzbek cuckoo wasp fauna counts 201 species and four subspecies in 23 genera and two subfamilies. One genus and 62 species are recorded for the first time for the country and six species resulted undescribed: Chrysis perfunctoria Rosa & Halada, sp. nov. (rufitarsis group), C. strejceki Rosa & Halada, sp. nov. (leachii group), C. storozhenkoi Rosa, Fateryga & Proshchalykin, sp. nov. (maculicornis group), Hedychridium frontipunctum Rosa & Proshchalykin, sp. nov. (flos group), Philoctetes gulbahra Rosa & Halada, sp. nov., and Spintharina zheztyrnak Rosa & Halada, sp. nov. We resurrect Chrysis gertabi Radoszkowski, 1891, stat. resurr. from the previous synonymy with C. mutabilis, and propose a new synonym C. hyrcana Semenov-Tian-Shanskij, 1967, syn. nov. of C. gertabi Radoszkowski, 1891.